2015
DOI: 10.1016/j.vph.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) counteracts the effects of Ang II on vascular smooth muscle cells, vascular remodeling and hemorrhagic stroke: Role of the NFкB inflammatory pathway

Abstract: Angiotensin (Ang)-(1-7) is a potential vasoprotective peptide. In the present study, we investigated its counteractive effects to Ang II on vascular smooth muscle cells (VSMCs) and intracerebral hemorrhagic stroke (ICH) through inflammatory mechanism. In in vitro experiments, human brain VSMCs (HBVSMCs) were treated with vehicle, Ang II, Ang II + Ang-(1-7), Ang II + A-779 or Ang II + Ang-(1-7) + A-779 (Mas receptor antagonist). HBVSMC proliferation, migration and apoptosis were determined by methyl thiazolylte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Vascular inflammation has been shown to induce brain hemorrhage in both humans and animal models. 26,27 Phosphate loading directly induced inflammation in vascular smooth muscle cells and increased the expression of matrix metalloproteinases II and IX and cathepsin S, 28,29 which degrade extracellular matrix and disrupt the integrity of vascular layers. Furthermore, phosphate loading also induced the apoptosis of vascular smooth muscle cells and endothelial cells via oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular inflammation has been shown to induce brain hemorrhage in both humans and animal models. 26,27 Phosphate loading directly induced inflammation in vascular smooth muscle cells and increased the expression of matrix metalloproteinases II and IX and cathepsin S, 28,29 which degrade extracellular matrix and disrupt the integrity of vascular layers. Furthermore, phosphate loading also induced the apoptosis of vascular smooth muscle cells and endothelial cells via oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other investigators showed that higher serum PTH tended to decrease the risk of brain infarction. 26 Given that malnourished subjects often show lower serum PTH levels, low PTH might, thus, be a manifestation of malnutrition, which is in turn associated with brain infarction. 35 The protein catabolic rate is often increased during inflammation, and a higher normalized protein catabolic rate might reflect systemic inflammation, which is in turn associated with an increased risk of brain infarction.…”
Section: September 2016mentioning
confidence: 99%
“…Indeed, studies from our laboratory demonstrate that AngII/AT 1 R activation may contribute to the vascular remodeling observed in T2D (11). Additionally, this AT 1 R-mediated activation of the VSMC by pro-inflammatory signaling may contribute to remodeling present in metabolic diseases (75, 76). …”
Section: Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…Collagen induced atherothrombosis [80]. Ang II was involved in apoptosis, inflammation [81], the neurological deficit score, hemorrhage volume [82], hypertrophy, and inward remodeling of cerebral arterioles [83]; after decreasing the Ang II levels, cerebral blood supply was improved [84], and ET-1 may promote the development of the stroke process [85]. ETAR and NO may be involved in the pathogenesis of cerebral vasospasm [37].…”
Section: The Potential Of Acupuncture For Secondary Prevention Of Strmentioning
confidence: 99%